2018
DOI: 10.1038/s41598-018-24759-4
|View full text |Cite
|
Sign up to set email alerts
|

High fat diet induces airway hyperresponsiveness in mice

Abstract: The experiment was conducted to examine the effect of a high fat diet (HFD) on airway hyperresponsiveness (AHR) in mice. Twenty-three adult male C57BL/6 J mice were fed with HFD or regular chow diet for two weeks. The total respiratory resistance was measured by forced oscillation technique at baseline and after methacholine aerosol challenge at 1, 3, 10 and 30 mg/mL. Bronchoalveolar lavage (BAL) was performed. Lipid levels and lipid peroxidation in lung tissue were measured along with gene expression of multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 23 publications
5
21
0
3
Order By: Relevance
“…Finally, our work establishes that allergic airway inflammation in obesity leads to alterations in the BM compartment and potentiate generation of proinflammatory lung DCs. In consistent with others, we found that HFD exacerbates airway inflammation, as indicated by an increase in BAL cellularity, plasma IgE, and IgG1 levels, and Th2/Th1 immune response (19,53,54). We show lung CD11b + conventional DCs, which are specialized for antigen presentation and to generate T cell-mediated immune responses in allergic asthma (55)(56)(57), notably increased by HDM sensitization.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, our work establishes that allergic airway inflammation in obesity leads to alterations in the BM compartment and potentiate generation of proinflammatory lung DCs. In consistent with others, we found that HFD exacerbates airway inflammation, as indicated by an increase in BAL cellularity, plasma IgE, and IgG1 levels, and Th2/Th1 immune response (19,53,54). We show lung CD11b + conventional DCs, which are specialized for antigen presentation and to generate T cell-mediated immune responses in allergic asthma (55)(56)(57), notably increased by HDM sensitization.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies generally focused on the airway responsiveness in obesity associated with asthma independent of sex. 30 Our results showed that a high-fat diet in female OVA-sensitized rats was very susceptible to AHR compared with male rats. Indeed, it is clear from the results that obesity in OVA-sensitized condition has the most impact on the tracheal responsiveness of females.…”
Section: Discussionmentioning
confidence: 55%
“…Previous studies suggest that obesity serves as a risk factor for the development, severity and weaker responsiveness to standard asthma medication . In the late‐onset non‐allergic phenotype of obesity‐associated asthma (LONA), airway hyperresponsiveness (AHR) is considered a consequence of lung compression and structural lung modifications due to increased body weight . Furthermore, animal models show that LONA is associated with T helper (Th)1‐ and Th17 aberrant immune responses .…”
Section: Introductionmentioning
confidence: 99%
“…3 In the late-onset non-allergic phenotype of obesity-associated asthma (LONA), airway hyperresponsiveness (AHR) is considered a consequence of lung compression and structural lung modifications due to increased body weight. 4,5 Furthermore, animal models show that LONA is associated with T helper (Th)1-and Th17 aberrant immune responses. 6,7 However, next to LONA, an early-onset allergic form of obesity-associated asthma has been described (EOA), 8 which is characterized by a more classical allergen-driven eosinophilia and Th2 differentiation without body weight-induced modulations.…”
Section: Introductionmentioning
confidence: 99%